Cognitive Features in Autistic Children without Intellectual Disability - M.M. Ivanova; L.G. Borodina (Moscow State University of Psychology and Education, 2020)
22 children with autism spectrum disorders (ASD) and 26 neurotypic children from 7 to 10 years old took part in the study of cognitive features of autistic children without intellectual disabilities. Instruments aimed at studying of cognitive functions in primary school children and free form narrative used in the research. Found that in children with ASD, some cognitive features significantly more pronounced than in neurotypical peers: lack of targeting, diverseness of thinking with a distortion of the generalization process, concreteness of thinking. The scores obtained in children with ASD were mainly within the mean values, while in the group of neurotypic children, for the most part, they were within high values. Revealed that children with ASD more often than neurotypic peers demonstrate a combination of specific thinking and some features that considered as characteristic of a schizophrenic pathopsychological complex of symptoms.